Chemical and Organoleptic Quality of Beef Sausage by Substitution of Tapioca with Kepok Banana (Musa paradisiaca formatypica) Flour - Mukhlisah, Andi Nurul; Ningtyas, Weny Dwi; Irfan, Muhammad; Syah, Setiawan Putra (Universitas Bengkulu, 2023)
One of the beef processing is sausage, which is well known in the community. At this time, the need for fast food (ready-to-cook) is increasing. The main ingredient used to produce sausages for stuffing is tapioca flour. The increasing price of tapioca flour is due to the high demand for its use in processed foods, so it is necessary to find alternative fillers that are more affordable. Kepok banana flour (Musa paradisiaca formatypica) has a starch content that is relatively similar to tapioca, so it can be used as an alternative raw material. This study aimed to determine the chemical and organoleptic quality of beef sausage made with Kepok banana flour. This study used a completely randomized design (CRD) consisting of 5 treatments, namely X0 = (control) 0% Kepok banana flour + 20% tapioca; X1 = 5% Kepok banana flour + 15% tapioca; X2 = 10% Kepok banana flour + 10% tapioca; X3 = 15% Kepok banana flour + 5% tapioca; X4 = 20% Kepok banana flour + 0% tapioca, with each treatment consisting of 4 replicates. The variables observed were protein content, moisture content, crude fibre, fat content, ash content and organoleptic of beef sausage. The results showed that the addition of Kepok banana flour in beef sausage processing had a significant effect (P<0.05) on protein content, fat content, moisture content, crude fibre, color, flavour, and aroma, but no significant effect (P>0.05) on ash content and texture of beef sausage. It is concluded that beef sausage made with kepok banana flour as a substitute for tapioca flour produces sausage with better chemical and organoleptic properties than beef sausage made with tapioca flour only. Kepok banana flour can be used as a filler in the production of beef sausage.